Personality Traits and Emotion Regulation Styles of Elite Beach Volleyball Dyads: Examination of Intra-Team Differences, Performance and Satisfaction Levels - Klatt, Stefanie; Rückel, Lisa-Marie; Wagener, Sebastian; Noël, Benjamin (Frontiers in Psychology, 2021)
The current study was designed to assess the personality traits and emotion regulation styles of elite beach volleyball players. Intra-team differences were examined with three primary objectives: (i) to create a personality profile of elite beach volleyball players, (ii) to examine the relationship of this profile in relation to performance and satisfaction levels, and (iii) to highlight the similarities in personalities of members of successful teams. A total of 82 elite beach volleyball players were asked to fill out the Big Five Inventory, the Personality Adjective Scale, and the Affective Style Questionnaire. Based on these, the overall satisfaction and performance level of these athletes were measured. Results indicated a higher manifestation of warmth, liveliness, emotional stability and reasoning, along with lower levels of neuroticism in successful athletes. The players used a variety of emotional regulation styles and reported being moderately to highly satisfied with their team. A repeated-measures MANCOVA revealed no significant differences in personality traits between the team members. This study generates valuable insights into the personality of elite beach volleyball players and can be useful for coaches, sport psychologists, and academics for practical application and further scientific research.